2015
DOI: 10.1016/j.hlc.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Peri-procedural Myocardial Infarction in the Era of High Sensitivity Troponin: A Validation of the Joint ACCF/AHA/ESC/WHF Universal Definition of Type 4a Myocardial Infarction with High Sensitivity Troponin T

Abstract: PMI as defined by the current Universal Definition using hsTnT is an independent predictor of adverse clinical outcome at 12 months in patients undergoing PCI. Accordingly, PMI remains a clinically relevant factor in current practice and should be considered a key outcome measure in clinical trials and a potential target for therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
1
19
0
2
Order By: Relevance
“…In a recently published article mild to moderate periprocedural myocardial injury was detected in 49.8% of the patients and severe myocardial injury was detected in 12.2% of the patients [16]. Some authors argue that high-sensitivity troponin measurement after PCI can be over-diagnostic; however, it has also been shown that patients with higher troponin levels have worse prognosis [4, 17]. Although there is controversy about the cut-off values for troponin and creatinine kinase (CK)-MB in the determination of PCI-related myocardial infarction [18], the third Universal Definition of Myocardial Infarction Guideline [19] recommended troponin measurement after PCI and defined myocardial infarction after PCI (type 4a MI) as a 5-fold increase of troponin with clinical or electrocardiographic evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recently published article mild to moderate periprocedural myocardial injury was detected in 49.8% of the patients and severe myocardial injury was detected in 12.2% of the patients [16]. Some authors argue that high-sensitivity troponin measurement after PCI can be over-diagnostic; however, it has also been shown that patients with higher troponin levels have worse prognosis [4, 17]. Although there is controversy about the cut-off values for troponin and creatinine kinase (CK)-MB in the determination of PCI-related myocardial infarction [18], the third Universal Definition of Myocardial Infarction Guideline [19] recommended troponin measurement after PCI and defined myocardial infarction after PCI (type 4a MI) as a 5-fold increase of troponin with clinical or electrocardiographic evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Although its clinical significance is controversial, it has been shown that even minor troponin elevations might be related to irreversible myocardial necrosis [3, 4]. Myocardial injury after PCI can occur due to side branch occlusion, distal embolization, and ischemia/reperfusion injury [2, 5].…”
Section: Introductionmentioning
confidence: 99%
“…To establish the diagnosis of PMI, a rise and/or fall of TnT of at least 1 value above the upper reference limit (14 ng/L) and either ischemic ECG changes or other aforementioned ischemic features were required. [18][19][20] Medical conditions potentially causing elevated TnT concentration (sepsis, acute kidney injury, stroke, and pulmonary embolism) were considered when establishing the diagnosis of PMI.…”
Section: Pmimentioning
confidence: 99%
“…Additionally, an increase greater than 3 times the 99th percentile URL appeared to predict an even worse prognosis, suggesting a dose-response relationship. Recent publications have shown that high sensitivity troponins perform similarly in this context, with elevations occurring in almost 30% of patients and also representing a worse outcome [10]. Thus, although some controversy exists regarding this issue, it is becoming increasingly evident than troponins should consistently be interpreted as a marker of myocardial necrosis after PCI, and therefore predicts adverse clinical events.…”
mentioning
confidence: 99%